Developing a Diagnostic Tool for a Prognostic Assessment of Resistance to Professional Information Stress in Flight Personnel - Геннадий Т. Красильников; Эльвира А. Крачко; Федор В. Мальчинский (Rossijskij psihologičeskij žurnal., 2021)
Introduction. Stress resistance is a professionally important quality for flight personnel. However, the methods for determining stress resistance (neuropsychic resistance) recommended by the regulatory documents for applicants to military flight schools are rather subjective. This paper presents a novel diagnostic tool as an objective instrument for assessing resistance to the effects of experimental information stress. Methods. The authors developed the diagnostic tool for assessing resistance to the influence of informational experimental stress intended for use in occupational psychological selection of flight personnel. A stressor represented a complex of stressful stimuli, including a competitive exam, complicated arithmetic tasks, and interferences having both noise and distraction effects. The level of stress resistance was determined by the dynamics of mental activity during testing, the physiological ‘cost’ of activity (heart rate at different stages of the experimental stress examination), and external behavior manifestations (speech, movements, posture, and facial expressions). The standardization procedure for a representative sample (n = 3191) used the Descriptive Statistics statistical software package, Microsoft Excel 2007. The author’s script of the diagnostic tool was incorporated into the software of the Reacor multifunctional psychophysiological complex. Results and Discussion. The study examined the applicability of the novel diagnostic tool for diagnosing applicants to military flight schools. The study sample comprised 1135 male candidates aged 18–27 years. The findings indicated the presence of a significant correlation between psychological, physiological, behavioral indicators of subjective stress resistance and the success of flight training (according to expert assessments of simulator training and flight practice). Therefore, the developed diagnostic tool for assessing resistance to experimental information stress is a sensitive test for diagnosing stress resistance and can be recommended for use in occupational psychological selection of flight personnel.